2018
DOI: 10.21815/jde.018.080
|View full text |Cite
|
Sign up to set email alerts
|

Dental Students’ Readiness to Address Adolescent Risk Behaviors: A Pilot Study

Abstract: Adolescents' engagement in risk-taking behaviors is well documented. However, the role of the dental practitioner in helping teenage patients understand and avert those behaviors is relatively unknown. The aim of this pilot study was to assess dental students' familiarity with adolescent risk behaviors, comfort level in discussing adolescent risk behaviors with teenage patients, and ratings of the relevance of these topics in dental education. Of the 373 University of Florida dental students across all four ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a previous study conducted at our institution, we found differences between preclinical (years one and two) and clinical students (years three and four) regarding comfort level and ratings of relevance 14 . To determine whether those findings would be observed at other dental schools, we expanded the study to include three additional institutions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a previous study conducted at our institution, we found differences between preclinical (years one and two) and clinical students (years three and four) regarding comfort level and ratings of relevance 14 . To determine whether those findings would be observed at other dental schools, we expanded the study to include three additional institutions.…”
Section: Discussionmentioning
confidence: 95%
“…With permission from the AAPD, we developed the questionnaire using a portion of the AAPD Pediatric Medical History–Supplemental for an adolescent patient along with other identified negative risk behaviors. The survey was previously administered to dental students across all four years at a single institution 14 . In previous studies, similar rating scale data have been treated as interval, so they are frequently analyzed using parametric techniques 13, 15, 16 …”
Section: Methodsmentioning
confidence: 99%